Physics in the structure and form of the architectural project. Museum of Contemporary Art Niterói, Brazil (2021)
This article analyzed the formal, functional, and structural aspects of the Museum of Contemporary Art Niterói in Brazil, by identifying the criteria associated with architecture and physics; this is to establish the importance of the analysis of the architectural project to obtain the basic skills of the architect. A mixed methodological framework was used, the quantitative phase was developed from a questionnaire under a non-probabilistic sample allowed to recognize the formal, structural, and functional aspects of the work under study, the qualitative phase used an interview that established the value represented by the recognition of the application of physics in architecture. As a relevant finding, it is highlighted a basic understanding of the physical elements applied to architecture, specifically in the case of Museum of Contemporary Art Niterói, Brazil, and that they recognize the importance of the analysis of architectural works as a pedagogical tool that favors obtaining the basic skills of the architect.